Níveis de zinco em dieta para codornas japonesas na fase inicial em dois ambientes térmicos - Moraes, Thiago de Assis (2018)
The objective of this study was to evaluate zinc levels (Zn) in the diet of Japanese quail from 1 to 42 days old maintained in two thermal environments on the zootechnical performance, intestinal morphology, hepatic glycogen, hepatic steatosis, carcass weight, organ weight and resistance bone of the tibia. 500 female quails were used, 250 of them in a thermal comfort environment and 250 in a heat stress environment, distributed in a completely randomized design in a factorial scheme (5 x 2), five levels of Zn (30, 60, 90, 120 e 150 mg / Zn per kg of feed). In the period from 1 to 21 days, increase in Zn levels resulted in reduced feed intake (WG) and worsening feed conversion (WG), while heat stress in the same phase decreased WP and worsened WC. In the total phase from 1 to 42 days there was interaction only for GP, showing that the increase of the Zn levels negatively influenced the GP of the birds created in heat stress, the CR and the AC presented worsening in the heat stress. There was interaction of the levels of Zn and the environment on the relationship vilo: crypt of the duodenum of the birds at 21 days of age, the unfolding showed linear decreasing effect as the Zn level increased in the comfort environment. At 42 days of age, the level of 150 mg / Zn presented the best relationship: duodenal crypt, the birds kept in thermal comfort also presented a better relationship vilo: crypt. The highest hepatic glycogen storage was observed at the level of 120 mg / Zn, and in a thermal comfort environment in the 21-day-old phase. At 42 days only the level of Zn was significant, with the highest glycogen stock also at 120 mg / Zn level. At 42 days the effect of Zn levels on hepatic steatosis was observed, the 90 mg / Zn level was the most positive for the absence of steatosis. At 21 days, liver and carcass weights were negatively influenced by the increase in Zn levels, heat stress decreased spleen, bursa, liver and carcass weights. For the 42 days, there was interaction on the spleen weight, presenting the highest weight at the level of 120 mg / Zn in the thermal comfort environment. The heat stress environment reduced liver and carcass weights. The tibial bone strength at 42 days increased linearly with increasing Zn levels and reduced heat stress. Based on the average of the performance variables found in the factorial regression equations, it is recommended to use 60 mg / Zn per kg in Japanese quail diets from 1 to 42 days of age in thermal comfort and heat stress.